Teacher Development in Managing Student Project-Based Research Learning for a Private Integrated Islamic Kindergarten - Maleeyan, Fitreeya; Sa-u, Samsoo (Journal of Islamic Studies, Prince of Songkla University, 2025)
Objectives: 1) To study the current state of project-based research learning management. 2) To develop teachers' skills in managing project-based research learning for students. And 3) To assess teachers' satisfaction with the improvement in project-based research learning management for students in a private integrated Islamic kindergarten. Methodology: This study adopted an action research approach aimed at enhancing teachers’ instructional practices. The sample group consisted of seven teachers. The research was conducted in four stages: planning, action, observation, and reflection. Data were collected through interviews and observations, along with the use of a training manual and a satisfaction questionnaire. Quantitative data were analyzed using percentage, mean, and standard deviation, while qualitative data were examined through descriptive content analysis. Research Findings: The findings revealed that 1. Most teachers continued to rely on lecture-based instruction and lacked the use of project-based learning activities. School administrators recognized the need to enhance teachers’ skills in planning, implementing, and assessing instruction through a project-based approach. 2. After the training, teachers demonstrated a better understanding and greater ability to apply project-based learning. Post-training scores were significantly higher than pre-training scores, and the quality of lesson plans in the second cycle was improved compared to the first. 3. Teachers reported a high level of satisfaction with the development process, indicating the effectiveness and positive reception of the training. Contributions: Educational institution administrators in private Islamic school can use the research results to train teachers in learning management, using research-based projects for students to adapt to their own context.